1974
DOI: 10.1901/jeab.1974.21-389
|View full text |Cite
|
Sign up to set email alerts
|

RESPONSE STRENGTH IN MULTIPLE SCHEDULES1

Abstract: In several different experiments, pigeons were trained with one schedule or condition of food reinforcement for pecking in the presence of one key color, and a different schedule or condition in the presence of a second key color. After responding in both of these multiple schedule components stabilized, response-independent food was presented during dark-key periods between components, and the rates of pecking in both schedule components decreased. The decrease in responding relative to baseline depended on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

37
431
7
57

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 379 publications
(532 citation statements)
references
References 34 publications
37
431
7
57
Order By: Relevance
“…Rachlin (1973) has proposed a non-quantitative theory of contrast similar to the dynamic model sketched out at the end of this chapter. In recent years, Nevin and his associated have elaborated a theory of behavioral "momentum" that can accommodate a wide range of contrast and choice phenomena (e.g., Grace, 1994;Nevin, 1974;Nevin, Tota, Torquato, & Shull, 1990) 12. Use of the term controlled to refer to the effect of a stimulus on a response is conventional, but it is not quite accurate.…”
Section: Theories Of Contrastmentioning
confidence: 99%
See 2 more Smart Citations
“…Rachlin (1973) has proposed a non-quantitative theory of contrast similar to the dynamic model sketched out at the end of this chapter. In recent years, Nevin and his associated have elaborated a theory of behavioral "momentum" that can accommodate a wide range of contrast and choice phenomena (e.g., Grace, 1994;Nevin, 1974;Nevin, Tota, Torquato, & Shull, 1990) 12. Use of the term controlled to refer to the effect of a stimulus on a response is conventional, but it is not quite accurate.…”
Section: Theories Of Contrastmentioning
confidence: 99%
“…I compare Herrnstein's approach to the problem of multiple schedules with an alternative proposed by Nevin and his associates and show the common features that underlie them. Nevin (1974), impressed by similarities between physical and behavioral "momentum," suggested that response strength is best understood not in terms of response rate but in terms of resistance to change. The idea is that a "stronger" response is not necessarily one that occurs at a higher rate but one that maintains its rate better in the face of challenge, i.e., has a higher behavioral "momentum" He tested this idea by arranging different conditions of food reinforcement in the presence of two or more successively alternating stimuli -components of a multiple schedule.…”
Section: Response Strengthmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, the influence of different dimensions of reinforcement on behavioral maintenance other than rate, such as magnitude of reinforcement, should be explored further. In an earlier study, Nevin (1974) observed that magnitude had similar effects as rate on 2 pigeons' response persistence. Rate of reinforcement was held constant at a Variable Interval (VI 1 min or VI 3 min) schedule, whereas duration of food availability varied from 7.5 s to 2.5 s. When free food was available, pigeon response rates were less resistant to change when reinforcement length was relatively less (i.e., 2.5 s), although 1 pigeon was equally persistent during VI 1 min regardless of the duration of reinforcement.…”
mentioning
confidence: 84%
“…Uma linha de pesquisa que aparentemente trabalha precisamente com essa questão é a do momento comportamental ou resistência à mudança (e.g., Lattal, 1989;Nevin, 1974;Nevin, Mandell, & Atak, 1983). Seria interessante que pesquisadores interessados em ambas as áreas, história comportamental e momento comportamental, desenvolvessem projetos conjuntos, em que tais questões possam ser sistematicamente avaliadas 8 .…”
Section: Os Efeitos Da História Podem Ser Permanentes?unclassified